Multicenter evaluation of membrane-based smear microscopy for detecting acid-fast bacilli in China - Xia, Hui (Int J Clin Exp Pathol, 2018)
Objective: To assess the feasibility and reliability of using membrane-based smear microscopy at peripheral laboratories in China. Methods: The clinical case control study was conducted in five tuberculosis (TB) dispensaries from September 2014 to May 2016. The membrane-based microscopy and direct smear microscopy were performed to compare the sensitivity, specificity, and the examination time for both methods was also analyzed. Results: A total of 5359 TB suspects were consecutively enrolled from 5 TB dispensaries, and 9915 specimens were finally analyzed. The sensitivity for membrane-based microscopy and direct smear microscopy was 76.9% (95% CI, 75.4-78.4) and 53.8% (95% CI, 52.1-55.6) respectively, and the specificity was 96.8% (95% CI, 96.4-97.2) and 99.2% (95% CI, 99.0-99.4) respectively. The sensitivity and specificity were both significantly different (P<0.001) between the two methods. The examination time for membrane-based smear microscopy (209.1±112.0 seconds) was significantly shorter than that for direct smear microscopy (253.1±79.4 seconds) (P<0.05). Conclusions: Membrane-based smear microscopy showed higher sensitivity and a shorter examination time in comparison with direct smear microscopy and it could be used at peripheral laboratories in China.